Moving beyond classroom teaching: a study of multidimensional teacher self-efficacy on job satisfaction and occupational commitment. Issue 7 (16th November 2020) - Huang, Xianhan; Lin, Chin-Hsi; Chi Kin Lee, John
ABSTRACT: Teacher self-efficacy is a key predictor of teacher attrition, but studies have primarily examined teacher self-efficacy via classroom teaching and overlooked other roles that teachers play in school. Accordingly, this study explores the relationships between, on the one hand, primary and secondary teachers' job satisfaction and occupational commitment and, on the other, their self-efficacy in three domains: classroom teaching, teacher-student relationships, and school decision-making. The participants included 1, 424 primary and secondary teachers from Shanxi, Xinjiang, and Chongqing, China. Confirmatory factor analysis was performed to ensure the validity of the survey instruments. The results of path analysis on the survey responses indicate that although all three types of self-efficacy showed a positive relationship with these teachers' satisfaction and commitment, self-efficacy in teacher-student relationships and self-efficacy in school decision-making both ranked as more important than self-efficacy in classroom teaching. The theoretical and practical implications of these findings are also discussed.